Legal Consequences of Mafqud (Missing Persons) Wealth According to Islamic Law - Zidan, Amidan; Angga, La Ode; Fataruba, Sabri (Faculty of Law, Universitas Pattimura, 2026)
Introduction: A missing person case occurred in one of the villages of Padaelo, Lalolang Village, Tanete Rilau District, Baru Regency, South Sulawesi, where a husband disappeared and after 8 years of disappearance he returned to his house which at that time had been sold by the heirs of his wife and child so that he also reported this to the local village government and the results of the report showed that the wife had sold her house and her inheritance in the form of rice fields and then she returned to her hometown.Purposes of the Research: Know and study the procedures for determining the assets of missing persons according to Islamic law and explain the legal consequences for assets according to Islamic law.Methods of the Research: The method used is normative legal research. The research approach is a statutory approach and a conceptual approach. Sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials is through literature study and then analyzed through a perspective using qualitative methods.Findings of the Research: The research results show that the mafqud's legal status must be determined by a judge through a court process before his assets can be distributed. As long as the status is not clear, mafqud assets must be frozen and cannot be transferred or distributed. The procedure for determining mafqud involves submitting an application by the heirs or interested parties to the Religious Court, taking into account the evidence and the circumstances of the person's disappearance. The legal consequences for Mafqud's assets depend on the judge's decision. If the mafqud is declared dead, his inheritance is distributed to the heirs according to the faraid provisions. However, if the mafqud returns, the property must be returned to him, unless it has been used legally. The role of judges is very important in creating legal certainty and protecting the rights of mafqud, heirs and interested parties.